2021
DOI: 10.1021/acsami.1c03935
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorbed Superoxide Species Enhanced the High Catalytic Performance of Ag/Co3O4 Nanocubes for Soot Oxidation

Abstract: The respective action mode between surface-adsorbed oxygen and bulk lattice oxygen during catalytic soot oxidation is still not fully recognized. Herein, a series of Ag-loaded Co3O4 catalysts with different Ag loading amounts were prepared by the impregnation method, and 5% Ag/Co3O4 presented competitive catalytic activity toward soot combustion with a T 50 below 290 °C in 10% O2/N2. This remarkable improvement in catalytic performance could be primarily attributed to the enhanced Ag–Co3O4 metal–support intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 56 publications
(205 reference statements)
0
20
0
Order By: Relevance
“…In the classic Langmuir–Hinshelwood theory, it is believed that reactants and oxygen are first co-adsorbed on the surface of a catalyst, and then oxygen gets electrons and reacts with reactants . Therefore, earlier attention was concentrated on tuning the adsorbed oxygen to improve the catalytic efficiency. In comparison, lattice oxygen in the bulk phase is considered to be too stable but it can selectively participate in some oxidation reactions. In addition, lattice oxygen is able to reduce competitive adsorption, has high safety, and is easy to replenish, and thus, it has the potential to replace gas-phase oxygen. , Nowadays, there are three main relationships between adsorbed oxygen and lattice oxygen in catalytic reactions, i.e., synergy, , primary/secondary effects, , and opposition/alone. More importantly, both adsorbed oxygen and lattice oxygen can realize mutual transformation under certain circumstances. Therefore, it appears as a crucial need to develop an operation-simple method to identify lattice oxygen and adsorbed oxygen in catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the classic Langmuir–Hinshelwood theory, it is believed that reactants and oxygen are first co-adsorbed on the surface of a catalyst, and then oxygen gets electrons and reacts with reactants . Therefore, earlier attention was concentrated on tuning the adsorbed oxygen to improve the catalytic efficiency. In comparison, lattice oxygen in the bulk phase is considered to be too stable but it can selectively participate in some oxidation reactions. In addition, lattice oxygen is able to reduce competitive adsorption, has high safety, and is easy to replenish, and thus, it has the potential to replace gas-phase oxygen. , Nowadays, there are three main relationships between adsorbed oxygen and lattice oxygen in catalytic reactions, i.e., synergy, , primary/secondary effects, , and opposition/alone. More importantly, both adsorbed oxygen and lattice oxygen can realize mutual transformation under certain circumstances. Therefore, it appears as a crucial need to develop an operation-simple method to identify lattice oxygen and adsorbed oxygen in catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…5−9 In addition, lattice oxygen is able to reduce competitive adsorption, has high safety, and is easy to replenish, and thus, it has the potential to replace gas-phase oxygen. 10,11 Nowadays, there are three main relationships between adsorbed oxygen and lattice oxygen in catalytic reactions, i.e., synergy, 3,12−14 primary/secondary effects, 15,16 and opposition/alone. 17−19 More importantly, both adsorbed oxygen and lattice oxygen can realize mutual transformation under certain circumstances.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Numerous catalysts for soot combustion have been reported using noble metals [7][8][9], perovskites [10,11], spinel-type oxides [12,13], hydrotalcites [14,15], alkaline metal oxides [16,17], transition metal oxides [18], and rare earth metal oxides [19]. Ag-based catalysts are promising candidates for catalytic soot oxidation reactions because of their low price among noble metals, and particularly the Ag 0 species has a high ability to activate oxygen [20][21][22]. Interestingly, the Ag 0 species can be automatically obtained by directly supporting Ag salt on reducible metal oxides (Co 3 O 4 , CeO 2 , MnO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Some reducible, noble metal-free metal oxides, such as CeO 2 and MnO 2 and particularly Co 3 O 4 , are active in soot oxidation [27]. Moreover, Co 3 O 4 exhibits a high ability for NO oxidation to NO 2 [22,28], which is a more effective oxidant than O 2 for soot oxidation. Thus, Co 3 O 4 becomes a good candidate for supporting noble metal catalysts in this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The slight decrease in soot catalytic activity may be due to the minor attenuation of the relative content of O ads /(O ads + O latt ). Chen et al also reported the catalytic soot performance of Ag/Co 3 O 4 and found that the decrease in adsorbed oxygen species was an important reason for the decrease of catalytic soot combustion [ 50 ].…”
Section: Resultsmentioning
confidence: 99%